Peningkatan Self Regulated Learning Siswa melalui Pelatihan Penggunaan Game Educandy Arabiy di Madrasah Ibtidaiyah Al Adnani Kayangan - Qomariyah, Lailatul; Niswah, Isniyatun; Qodir, Abdul; Mu’at, Mu’at; Bahrodin, Ariga; Hakim, Luthfi; Ilahiyah, Iva Inayatul (Universitas Nusantara PGRI Kediri, 2024)
Self Regulated Learning has an important role to help students be more independent in learning, both in setting schedules, targets and strategies to achieve them. This training in using the Educandy game aims to make it easier for students to improve their Arabic language learning achievements due to a decrease in students' SRL. Therefore, learning Arabic using educational games is very necessary because it suits students' preferences. The method of implementing this service is the Service Learning method, namely investigation, preparation, training and mentoring and reflection. The results of the training showed that 69% of students were very satisfied and 22% of students were satisfied with the training activities and had provided benefits in improving students' achievements and SRL. which is indicated by their attitude of independence and self-confidence individually being able to complete all stages of the game. These results have an impact on the realization of one of the students' Pancasila profiles, namely the independent dimension with a form of self-regulation.